An Analysis of : Embedded Systems in Embedded Processors Knack - Talawar, Arun K; Malaj, Sunita S; Hiremath, Raju (Gyan Management Journal, 2023)
The mechanisms via way of means of which software program interacts  with the bodily international are converting rapidly. Today’s fashion is  “smart” sensors and drives with microprocessors, community interfaces  and software program that permit far flung get entry to to sensor  records and far flung unit activation. There is likewise the Internet of  Things (IoT), Industry 4.0, Industrial Internet, Machine to Machine,  Internet of Everything, Smart Planet, TSensors (trillions of sensors)  or Fog (similar, however towards the cloud). Earth is an expression of  era that deeply connects our bodily and informational worlds. In the  IoT international, the interfaces among those worlds are stimulated  and derived from statistics era, specially net era. Our recognition  is on interacting with the bodily surroundings wherein software  program and hardware operate. This calls for a unique modeling of  the time dynamics of the software program and networks and a clean  specification of the parallel nature of the application. The truth that  implementation era has now no longer but reached this factor need to  now no longer educate a incorrect technonical approach. All need to  learn design and modeling and enrich them with a critical reflection on  what it is. Today’s embedded systems technology should be presented  in a neutral way, not as a collection of facts and tricks, as in many of  the recent trends in, but as a cornerstone to a better design experience.
Keywords: Embedded System; Processors; VLIW; Microcontrollers